Non‐HIV‐related health care utilization, demographic, clinical and laboratory factors associated with time to initial retention in HIV care among HIV‐positive individuals linked to HIV care. Issue 4 (28th July 2015) - Lourenço, L; Nohpal, A; Shopin, D; Colley, G; Nosyk, B; Montaner, JSG; Lima, VD
Abstract : Objectives: The aim of the study was to explore non‐HIV‐related health care service (NHRHS) utilization, demographic, clinical and laboratory factors associated with timely initial "retention" in HIV care among individuals "linked" to HIV care in British Columbia (BC), Canada. Methods: We conducted a Weibull time‐to‐initial‐retention analysis among BC Seek and Treat for Optimal Prevention of HIV/AIDS (STOP HIV/AIDS) cohort participants linked in 2000–2010, who had ≥ 1 year of follow‐up. We defined "linked" as the first HIV‐related service accessed following HIV diagnosis and "retained" as having, within a calendar year, either: (i) at least two HIV‐related physician visits/diagnostic tests or (ii) at least two antiretroviral therapy (ART) dispensations, ≥ 3 months apart. Individuals were followed until they were retained, died, their last contact date, or until 31 December 2011, whichever occurred first. Results: Of 5231 linked individuals (78% male; median age 39: (Q1−Q3: 32–46) years], 4691 (90%) were retained [median time to initial retention of 9 (Q1–Q3: 5–13) months] by the end of follow‐up and 540 (10%) were not. Eighty‐four per cent of not retained and 96% of retained individuals used at least one type of NHRHS during follow‐up. Individuals who saw a specialist for NHRHS during follow‐up had a shorter time to initial retention than those who did not [adjusted hazard ratio (aHR) 2.79; 95% confidence interval (CI): 2.47–3.16]. However, those who saw a general practitioner (GP) for NHRHS (aHR 0.79; 95% CI: 0.74–0.84) and those admitted to the hospital for NHRHS (aHR 0.60; 95% CI: 0.54–0.67), versus those who did/were not, respectively, had longer times to initial retention, as did female patients, people who inject drugs (PWID) and individuals < 40 years old. Conclusions: Overall, 84% of not retained individuals used some type of NHRHS during follow‐up. Given that 71% of not retained individuals used GP NHRHS, our results suggest that GP‐targeted interventions may be effective in improving time to initial retention.